Computational Identification of Pyrrole Ring C as the Preferred Donor for Excited‐State Proton Transfer in Bacteriophytochromes. Issue 6 (30th March 2018) - Falklöf, Olle; Durbeej, Bo
Abstract: The engineering of bacteriophytochrome photoreceptors into near‐infrared fluorescent proteins is a promising route toward deep‐tissue imaging of living cells with many challenges ahead. One key objective is to increase the fluorescence quantum yields, which are limited by competing non‐radiative relaxation processes involving not only the well‐known double‐bond photoisomerization of the tetrapyrrole chromophore, but also a potential excited‐state proton transfer from the chromophore to the protein. Motivated by the lack of mechanistic knowledge about this proton transfer, we here use hybrid quantum mechanics/molecular mechanics methods to investigate three possible scenarios for how the process is initiated. Through calculated excited‐state p K a values of the chromophore inside the protein matrix of Deinococcus radiodurans bacteriophytochrome, it is found that pyrrole ring C is a much more likely donor for excited‐state proton transfer than rings A and B, which are also possible donors discussed in the literature. This finding offers a starting point for establishing a strategy to strengthen the fluorescence of engineered bacteriophytochromes through biochemical inhibition of the proton transfer. Abstract : A, B, or C? Hybrid quantum mechanics/molecular mechanics methods are used to identify the most likely chromophore donor moiety (pyrrole ring A, B, or C) for the excited‐state proton transfer believed to limit the fluorescence quantum yields that can be attained in the engineering of bacteriophytochrome photoreceptor proteins into near‐infrared fluorescent proteins.